FRI0477 STUDY OF CORTICAL AND TRABECULAR COMPARTMENTS THROUGH 3D-SHAPER IN LUNG TRANSPLANTED PATIENTS. (June 2019) - Barceló-Bru, Mireia; Erra, Alba; Espinet, Carina
Abstract : Background: Osteoporosis in lung transplant (LT) patients is a frequent complication. Glucocorticoid treatment (GC) is a prominent risk factor (RF) that alters both bone mass and architecture. Studying the volumetric BMD using 3D-SHAPER software would help the study of architecture. Objectives: To study the change in cortical surface density, volumetric trabecular density and integral volumetric density measured by 3D-SHAPER before and after LT as well as changes in bone mineral density (BMD) measured by densitometry (DXA). Methods: LT patients assessed in Rheumatology are included. The demographic characteristics, diagnosis of lung disease and RF of low bone mass prior to LT are collected. Patients were grouped into 3 groups according to the type of disease, these being: Chronic Obstructive Pulmonary Disease (COPD), Interstitial Lung Diseases (ILD) and OTHER pathologies. Bone mass was evaluated by DXA (GE-LUNAR) before and 6 months after LT and 3D-SHAPER software (v2.7, Galgo Medical) was applied in all DXAs. Results: 49 LT patients were included (46.9% women), with an average age of 56.9 ± 8.7 years. In the ILD group, a higher proportion of patients with a low calcium intake (p = 0.027) and with high doses of GC (p = 0.001) was observed. COPD group presented the highest proportion of smokers (p = 0.027). Prevalence of osteoporosis prior to LT was 24.5%, higher in COPD (p=0.007). Values of BMD and 3D-SHAPER as well as the percentage of post-transplant variation are shown in Table 1 . Of the 47 patients, 19 (38.8%) started osteoactive treatment before LT, with a higher percentage of patients treated in the COPD group (p = 0.007). Of 42 patients, we have DXA at 6 months post-transplant, with a prevalence of osteoporosis of 23.8%. 27/42 patients underwent post-transplant osteoactive treatment, with an average treatment time until DXA was 19.2 ± 26.1 months, with no differences between groups. Conclusion: Prevalence of low bone mass is high both before and after the transplant. Prevalence of some osteoporosis RFs was different between the lung disease groups. COPD group presented a worse bone mass before LT. Subsequently, they experienced a significant improvement in BMD and volumetric measurements with respect to the other two groups, which showed losses of these parameters. COPD was the group most treated for osteoporosis and with a lower proportion of patients with GC at high doses. Trabecular BMDv was the most altered measure of 3D-SHAPER, with greater decrease in patients with GC at high doses and lower in those with osteoactive treatment. Disclosure of Interests: None declared